Análisis De Los Efectos Que Se Producen Al Utilizar Repuestos Genéricos En El Sistema De Control De Emisiones Del Chevrolet Sail 1,4l 2012 - Noroña Merchan, Marco Vinicio (2017)
This article aims to analyze if using generic spare parts in the vehicle Chevrolet Sail 1.4L specifically the engine air intake filter, the spark plugs and modifying the calibration of the spark plug electrodes we managed to reduce the percentage of emissions of pollutant gases to the environment.The importance of controlling emissions of polluting gases for the wellbeing of humans and ourplanet. At present the ozone layer is deteriorated products of harmful gases that cause the greenhouse effect. Combustion in the engines is the main cause of environmental pollution, so the electronics and other devices have been implemented to control and reduce the pollution generated by combustion in the engines. There were 192 laboratory tests where 4 different engine air intake filters were used, one with the original and the other with threeother brands (Shogun, Samurai and Tecfil), 4 different brands of spark plugs were used, one of them being the original one Of the vehicle (champion) and the other three are of alternating marks (Bosch, NGK and Denso), within the laboratory tests it was contemplated to carry out 3 calibrations to the electrodes the first to0.7mm the second to 0.85mm and the third And last to 1mm. Laboratory tests consist of making all possible combinations of air filters, spark plugs and calibrations to observe the trend of the percentage of exhaust gas contamination to the environment, after obtaining the results of the laboratory tests will tabulate the values for Determine which are the parts with which the Chevrolet Sail 1.4L vehicle emits the lowest percentage of exhaust gases to the environment. These data are the result of our research in which this project consists and will be our contribution to the community to take it as an option when performing the maintenance of your vehicle and will also be an option when doing the vehicle reviewwhere theregulator senses the contamination of gases emitted in the vehicle